Analysis Forecasting Sales With Single Exponential Smoothing Method - Abraham Manalu; Dewi Roito; Eika Rizkiadina; Yonata Laia (LPPM Universitas Bina Sarana Informatika, 2022)
Currently, as we know, with the use of computer-based systems, almost everyone's activities depend on computer-based systems. One of the now very acceptable uses of the application is the sales system. In this research, the problem faced is the difficulty of determining the amount of inventory stock each month. The reason is the number of types of goods that are not small. This is what the researcher wants to solve the problem with the single exponential smoothing method. Because the method used can do fortune-telling in the short term, for example, one month ahead. The results of this study succeeded in predicting the amount of inventory in stock every month.